Addendum to "The well-posedness of a swimming model in the 3-D incompressible fluid governed by the nonstationary Stokes equation" - Khapalov, Alexander (Zielona Góra: Uniwersytet Zielonogórski)
In this addendum we address some unintentional omission in the description of the swimming model in our recent paper (Khapalov, 2013).
Keywords: swimming models; coupled PDE/ODE systems; nonstationary Stokes equation